“Thinking along the margins”: the choreography of trauma in The Body Artist, by Don DeLillo - Sylvie Bauer (Sillages Critiques)
The two structuring events of The Body Artist, Rey Robles’s death and the performance of Laura Hartke, his grieving wife, are the indissociable ellipses around which Don DeLillo’s novel is built. Mourning and performing become therefore intimately linked, in a process that seems to keep the real in abeyance. It is within this sense of suspension that the blanks in the narrative take place, forming the margins along which the main character and the reader try to make sense of events that escpe the power of language.